New data on the taxonomy, distribution and ecology of the genus Peniophora Cooke (Basidiomycota, Fungi) in the Republic of Macedonia - Lambevska, Aneta; Rusevska, Katerina; Karadelev, Mitko (Macedonian Journal of Ecology and Environment, 2013)
This is the first systematic research of genus Peniophora in the Republic of Macedonia. Out of the total number of 36 species of this genus known in Europe, within the investigations in the Republic of Macedonia, the following 22 species have been recorded: Peniophora cinerea, P. erikssonii, P. incarnata, P. junipericola, P. laeta, P. lilacea, P. limitata, P. lycii, P. meridionalis, P. nuda, P. piceae, P. pini, P. pithya, P. proxima, P. quercina, P. rufomarginata, P. tamaricicola, P. violaceolivida. Four species: P. polygonia, P. pseudoversicolor, P. versicolor и P. versiformis has been recorded for the first time for mycobiota of Macedonia. This review considers aspects of the taxonomy, distribution and ecological features of Peniophora species in the Republic of Macedonia.